Constructing the sex trafficker: spectral figures and sexual violence in California's Proposition 35. Issue 3 (2nd July 2016) - HoSang, Daniel Martinez; Yamin, Priscilla
Abstract: This article examines the development, framing, and implementation of Proposition 35, the 'Californians Against Sexual Exploitation Act.' The 2012 ballot initiative, described variously as a measure against human slavery, human trafficking, and sex trafficking secured more votes than any other initiative or candidate in a single statewide election in California history. We argue that the measure exemplifies a disjuncture in the articulation of feminist politics against sexual violence, labor exploitation, and criticisms of the carceral state. The rise of the sex trafficker as a 'spectral' subject of contemporary political discourse shapes a broader ideological framework that permits a distinct set of political actors and interests to widen their institutional and political authority and to marginalize competing claims about the roots of sexual violence and labor exploitation. Proposition 35, which targets a 'spectral' figure abstracted from institutional context and relations of power, expands the carceral state in the name of protecting vulnerable women while also excluding long-standing feminist solutions to sex and gender-based violence.